Pemikiran Fikih Ibn Taimiyyah dan ‎Pengaruhnya ‎ pada Era Modern di Arab Saudi - Abu Azam Al Hadi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
The thought of Ibn Taimiyyah is empirical in nature. He is known as an Islamic scholar with rationalistic inclination who believes that the truth exists in reality, not in one’s mind. He also believes that there is no contradiction between right human mind and revealed texts. Logic as deductive method of thinking cannot be used as a tool to accurately examine Islamic objects. Empirical Islamic objects can only be discevered through experiments and observation. Ibn Taimiyyah is also a salaf adherent whose method of thinking is originated strictly on the Qur’an and the Sunna. He tried to renew the perception and application of Islamic teaching in puritanism manner. Consequently, his renewal is reformative as well as modern. It can be said that it is a combination of conservative traditionalism and progressive modernity